ENGLISH TEACHER'S PERSPECTIVES ON STUDENT CENTERED APPROACH IN SUPPORTING ENGLISH LANGUAGE LEARNING - Balliya, Balliya; Diana, Novita; Farizawati, Farizawati (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2025)
This study aims to investigate English teachers’ perceptions of the implementation of the Student-Centered Approach (SCA) in English language teaching at the junior high school level. The Student-Centered Approach emphasizes the active role of students in the learning process, encouraging greater student autonomy, creativity, collaboration, and engagement in the classroom. In contrast to traditional teacher-centered methods, SCA shifts the focus from the teacher to the students, allowing them to take responsibility for their own learning. This research employed a qualitative method involving interviews, classroom observations, and documentation. The participants in this study were six English teachers at Sukma Bangsa Pidie Schools, a private School in Aceh, Indonesia. The data were analyzed using thematic analysis to identify patterns and themes in the teachers’ responses. The results showed that most teachers had a positive perception of the Student-Centered Approach and had implemented various strategies such as group discussions, project-based learning, student presentations, and interactive games. However, several challenges were also identified, including limited time, lack of teaching resources, large class sizes, and varying levels of student motivation and proficiency. Despite these challenges, the teachers believed that the Student-Centered Approach was effective in increasing student participation and improving language skills. The study suggests the need for continuous professional development to support teachers in applying student-centered practices more effectively.